Autologous Hematopoietic Stem Cell Transplantation May Reverse Renal Failure in Patients with Multiple Myeloma - Parikh, Gaurav C. (2009)
Approximately 20% of patients with multiple myeloma (MM) have renal failure at diagnosis, and about 5% are dialysis-dependent. Many of these patients are considered ineligible for autologous hematopoietic stem cell transplantation (auto-HSCT) because of a high risk of treatment-related toxicity. We evaluated the outcome of 46 patient with MM and renal failure, defined as serum creatinine >2 mg/dL sustained for >1 month before the start of preparative regimen. Patients received auto-HSCT at our institution between September 1997 and September 2006. Median serum creatinine and creatinine clearance (CrCl) at auto-HSCT were 2.9 mg/dL (range: 2.0–12.5) and 33 mL/min (range: 8.7–63), respectively. Ten patients (21%) were dialysis-dependent. Median follow-up in surviving patients was 34 months (range: 5–81). Complete (CR) and partial responses (PR) after auto-HSCT were seen in 9 (22%) and 22 (53%) of the 41 evaluable patients, with an overall response rate of 75%. Two patients (4%) died within 100 days of auto-HSCT. Grade 2–4 nonhematologic adverse events were seen in 18 patients (39%) and included cardiac arrythmias, pulmonary edema, and hyperbilirubinemia. Significant improvement in renal function, defined as an increase in flomerular filtration rate (GFR) by 25% above baseline, was seen in 15 patients (32%). Kaplan-Meier estimates of 3-year progression-free survival (PFS) and overall survival (OS) were 36% and 64%, respectively. In conclusion, auto HSCT can be offered to patients with MM and renal failure with acceptable toxicity and with a significant improvement in renal function in approximately one-third of the transplanted patients. In this analysis, a melphalan (Mel) dose of 200 mg/m(2) was not associated with an increase in toxicity or nonrelapse (Mel) mortality (NRM).